2020
DOI: 10.1002/jpen.1962
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition During Critical Care: An Audit on Actual Energy and Protein Intakes

Abstract: Introduction: Oral nutrition is delivered frequently in intensive care units (ICUs) but rarely studied. The primary objective of this study was to quantify nutrition intakes in patients exclusively orally fed (OF) and in those receiving medical nutrition solutions or both. Methods: Adults who stayed in a mixed ICU for ≥3 days were studied. Nutrition deficits were calculated as the difference between estimated energy or protein targets (determined by weight-based formulas) and actual intakes (recorded on a dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…The impact of nutrition on the functional recovery of critically ill patients remains unclear. Prior studies have shown inconsistent effects, presumably due to variabilities in the assessment of muscle function, different follow-up times, large drop-out rates, and, in some cases, di culties to obtain data post ICU/hospital discharge (12,35,(39)(40)(41). In our study, the associations of macronutrient intakes with IMS values could not be assessed because of a ceiling effect, not allowing to identify differences in IMS values in patients able to walk independently.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The impact of nutrition on the functional recovery of critically ill patients remains unclear. Prior studies have shown inconsistent effects, presumably due to variabilities in the assessment of muscle function, different follow-up times, large drop-out rates, and, in some cases, di culties to obtain data post ICU/hospital discharge (12,35,(39)(40)(41). In our study, the associations of macronutrient intakes with IMS values could not be assessed because of a ceiling effect, not allowing to identify differences in IMS values in patients able to walk independently.…”
Section: Discussionmentioning
confidence: 88%
“…A speci c limiting effect was the extremely varying design, patient selection and analytical approaches of clinical studies giving room to different interpretations (33). Limitations of observational studies result from an inadequate ratio between the number of events and confounding variables, and from the ignorance of confounding by indication, competing risks, time-dependency of macronutrient intake, and time-variation/non-linearity of associations, causing a considerable bias (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is plausible that nutrition may be important, the limited data available indicate that both energy and protein intake during this period is worse than in the early ICU period for factors relating to patients, clinicians and system issues. [9][10][11][12][13][14][15] A cumulative energy deficit because of inadequate energy delivery after ICU discharge, coupled with the deficits observed during the ICU period, may be an explanation for the lack of benefit observed in critical care nutrition trials to date.…”
Section: Open Accessmentioning
confidence: 99%
“…Later in intensive care unit (ICU) stay and throughout the subsequent hospital admission may be a time when the amount of energy and protein is important for recovery, with metabolism changing to allow exogenous nutrition to be processed. Although it is plausible that nutrition may be important, the limited data available indicate that both energy and protein intake during this period is worse than in the early ICU period for factors relating to patients, clinicians and system issues 9–15. A cumulative energy deficit because of inadequate energy delivery after ICU discharge, coupled with the deficits observed during the ICU period, may be an explanation for the lack of benefit observed in critical care nutrition trials to date.…”
Section: Introductionmentioning
confidence: 99%
“…According to the few studies published so far, critically ill patients who were fed orally had very low intakes in term of both energy and proteins, compared to predicted requirements and recommendations [5,[16][17][18][19][20], regardless of the underlying cause. In the different studies, energy intakes varied from 30 to 50% of the daily requirement or prescription.…”
Section: Oral Nutrition During and After Critical Illnessmentioning
confidence: 99%